Comments on R. Karbe and R. L. Kerlin (2002), Cystic Degeneration/Spongiosis Hepatis (Toxicol Pathol 30 (2), 216-227) - Bannasch, Peter (Toxicologic pathology, 2003)
Karbe and Kerlin have questioned the classification of spongiosis hepatis as a preneoplastic lesion or even a benign neoplasm, designated as spongiotic pericytoma, and have proposed to use the term cystic degeneration for this lesion in rats and fish. However, the reclassification of spongiosis as cystic degeneration is unwarranted for several reasons. In the rat, spongiosis hepatis represents a specific pathomorphologic entity, originating from the perisinusoidal (Ito) cells; it may occur spontaneously in aged animals but its number and size increases significantly after exposure to various (hepato)carcinogens. Comparative morphological, immunohistochemical, and autoradiographic studies in rats exposed to N -nitrosomorpholine revealed that spongiosis hepatis is an integral part of larger proliferative Ito-cell aggregates showing an autonomous, progressive growth. The classification of spongiosis hepatis as a benign neoplasm is based on these findings that endorse and extend previous considerations on the preneoplastic or neoplastic nature of this lesion. Irrespective of the classification of spongiosis hepatis as a benign neoplastic or a preneoplastic lesion, there is compelling evidence for its reliability as a sensitive marker for (hepato)carcinogenic effects in rats and fish. The data collected by Karbe and Kerlin support rather than contradict the reliability of spongiosis hepatis as an effect marker for carcinogens.